Mirror therapy in the neuroadaptive training paradigm in rehabilitation and potential mechanisms of neural remodeling: a 20-year bibliometrics analysis - Wang, Yinkai; Guan, Chong; Li, Haozheng; Wei, Bokai; Lv, Xiuqin; Yang, Guohui; Yang, Qian; Geng, Chao; Gao, Jingying; Yu, Zixuan; Sun, Tianbao (Frontiers in Psychology, 2025)
ObjectiveMirror Therapy activates mirror neurons, promotes neural connection regeneration, promotes brain reorganization and motor recovery, and alleviates limb pain. This study uses bibliometric methods to analyze the research trends of Mirror Therapy, aiming to fill the current research gap and provide valuable insights and suggestions for future research.MethodsPublications related to mirror therapy from 2004 to 2024 were retrieved from the Web of Science Core Collection database. Data visualization and analysis were performed using CiteSpace, VOSviewer, and Scimago Graphica.ResultsWe included 728 papers in the analysis and noted an increasing trend in annual publication volume. Collaboration network analysis revealed close cooperation among scholars from these major countries and institutions. The high-frequency reference vocabulary related to mirror therapy is grouped through a clustering network, revealing the main directions and hotspots of research. Keyword burst analysis reveals current research trends, including mechanism exploration, clinical applications, and clinical treatment areas.ConclusionA 20-year bibliometric analysis of mirror therapy literature highlights its global expansion and diversification, particularly in neurology and rehabilitation, emphasizing its importance in pain relief and post-stroke recovery, with future interdisciplinary research focusing on biomarkers and neuroimaging to refine its clinical effectiveness.